Changes consequent to maxillary molar distalization with the bone-anchored pendulum appliance - Aldo Otazú Cambiano; Guilherme Janson; Acácio Fuziy; Daniela Gamba Garib; Diego Coelho Lorenzoni (Wolters Kluwer Medknow Publications, 2017)
Objectives: This retrospective study aimed to evaluate the dentoalveolar, skeletal, and soft tissue effects obtained with bone-anchored pendulum appliance in patients with Class II malocclusion. Materials And Methods: A total of 18 patients (4 male, 14 female) at a mean pretreatment age of 14.0 years (+1.08) were enrolled in this study. All patients were treated with the bone-anchored pendulum appliance for an average duration of 4.8 months. Only the active distalization period was evaluated with predistalization and postdistalization lateral cephalograms. Skeletal, dentoalveolar, and soft tissue variables were obtained. Based on these variables, the treatment effects were evaluated with dependent t-test. Results: Correction of Class II molar relationship resulted from distal movement of 3.45 mm and tipping of 11.24° of the first maxillary molars. The premolars were distalized accompanying the molars. Conclusions: The bone-anchored pendulum appliance proved to be an effective method for distalization of maxillary molars in cases that require maximum anchorage, avoiding reciprocal mesial movement of premolars and incisors.